the source. (American Libraries)
Presents news updates concerning library science in the United States compiled as of January 1981. Pennsylvania-based Free Library of Philadelphia's launch of a project to promote libraries to inner city children; Publication of 'Videodisc News,' a monthly journal which covers videodisc uses, services, programming hardware and software.